1998
DOI: 10.1139/v98-115
|View full text |Cite
|
Sign up to set email alerts
|

Article

Abstract: The preparation, characterization, properties, and reactivity of a novel quantum-confined CdS nanocluster containing a chemically active aniline surface are described, along with three general methods for the covalent attachment of a wide scope of molecular moieties to the cluster surface. The formation of facile covalent linkages via DCC mediated amidization, secondary amine formation, and thiourea condensation is discussed and, as the introduction of surface functionality is crucial for the eventual realizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…81 Also, the surface states of smaller particles can be easily stabilized due to a large percentage of atoms on or near the surface as well as a higher curvature and show less PL emission due to the more efficient transfer of electrons to suitable species adsorbed on the surfaces. On the other hand, it has been demonstrated by Fogg et al 82 and Veinot et al 83 that the coordination of electrondonating compounds, such as an amine and phosphine oxide, significantly improves the PL performance of CdS NPs. Therefore, the anionic surfactants are expected to produce CdS NPs with a better PL emission when compared to cationic surfactants.…”
Section: Pl Emissionmentioning
confidence: 98%
“…81 Also, the surface states of smaller particles can be easily stabilized due to a large percentage of atoms on or near the surface as well as a higher curvature and show less PL emission due to the more efficient transfer of electrons to suitable species adsorbed on the surfaces. On the other hand, it has been demonstrated by Fogg et al 82 and Veinot et al 83 that the coordination of electrondonating compounds, such as an amine and phosphine oxide, significantly improves the PL performance of CdS NPs. Therefore, the anionic surfactants are expected to produce CdS NPs with a better PL emission when compared to cationic surfactants.…”
Section: Pl Emissionmentioning
confidence: 98%
“…Since the use of ligand-conjugated QDs as fluorescent biolabeling reagents was reported in 1998 by the groups of Alivisatos [51] and Nie [52], many approaches to QD applications have been realized in the bioanalytical field such as DNA sequencing, tissue immune-diagnostics and single molecular imaging [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The advantages of QDs as biolabeling agents are (i) tunability of the emission wavelength by changing the particle size, (ii) a sharp and symmetrical emission peak, (iii) the high intensity and long lifetime of the fluorescence and (iv) a wide range of excitation wavelengths.…”
Section: Preparation Of Cds Quantum Dots By Co-precipitation In the Pmentioning
confidence: 99%
“…Several approaches to fluorescence activation based on the confinement of charge carriers within the QD cores have been reported [59][60][61][62]. For example, the coordination of electron-donating compounds such as amines and phosphine oxide significantly increases the fluorescence intensity [63,64]. In the case of QD stabilization by the PAMA homopolymer, the amino groups in the side chain of PAMA were used not only for coordination on the CdS surface but also for solubilization in the aqueous phase.…”
Section: Preparation Of Cds Quantum Dots By Co-precipitation In the Pmentioning
confidence: 99%
“…Pietro and co-workers reported that certain organic-capped CdSe nanocrystals lost fluorescence upon photoexcitation due to a loss of electrons from the nanocrystals through the organic ligands [4]. Guyot-Sionnest and co-workers have recently described the quenching of band-edge luminescence in organically capped CdSe nanocrystals via the injection of electrons into the nanocrystals using sodium biphenyl [5].…”
Section: Resultsmentioning
confidence: 99%